Ultrasound measurement of knee synovial fluid during external pneumatic compression. Issue 3 (12th February 2019) - Meehan, Richard; Wilson, Chris; Hoffman, Eric; Altimier, Lynne; Kaessner, Maryanne; Regan, Elizabeth A.
ABSTRACT: Synovial fluid based biomarker research has been limited by the small volumes of synovial fluid from the knees of some patients. We used ultrasound (US) to determine if synovial fluid could be displaced into an access port during pneumatic compression to 100 mmHg. Forty knees from 37 consecutive arthritis patients with rheumatoid arthritis −25, osteoarthritis −8, psoriatic arthritis −2, and 1 each with systemic lupus erythematosus and gout were evaluated. This group of 28 females and 9 males with a median age of 59 years and an average body mass index of 26.9 kg/m 2 had previously undergone a diagnostic arthrocentesis and or a therapeutic knee injection using this pneumatic compression device. Blinded digital image analysis of the anechoic region on ultrasound demonstrated an increase in fluid within the 9 cm × 6 cm access port (anterolateral or anteromedial joint) during inflation in all patients with a 2.5–3.5 fold increase in fluid area and a 2–3 fold increase in fluid depth after inflation, p < 0.001. Statement of clinical significance: External pneumatic compression to the knee provides a larger volume of synovial fluid under positive pressure which should allow investigators to achieve greater success in obtaining synovial fluid during arthrocentesis for biomarker research or provide more precise therapeutic injections than traditional non image‐guided anatomical landmark‐based techniques. © 2019 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res